2006
DOI: 10.1016/j.jacc.2005.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Training Decreases B-Type Natriuretic Peptide Expression and Adrenergic Activation in Patients With Heart Failure

Abstract: Clinical benefits after physical training in patients with HF are associated with blunting of adrenergic overactivity and of natriuretic peptide overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 18 publications
12
155
1
2
Order By: Relevance
“…25,26 Certainly, this scenario appears likely in cardiac failure where aerobic training decreases both circulating norepinephrine and NT-proBNP levels. 27 Any such associations are potentially important for UAE nationals since, as in our report, earlier studies suggest that physical activity levels are particularly low in this population 28,29 and may be linked to high levels of obesity and hypertension. 28,30 Regarding our second observation, there is little information, to our awareness, relating circulating levels of the cardiac natriuretic peptides to ethnicity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…25,26 Certainly, this scenario appears likely in cardiac failure where aerobic training decreases both circulating norepinephrine and NT-proBNP levels. 27 Any such associations are potentially important for UAE nationals since, as in our report, earlier studies suggest that physical activity levels are particularly low in this population 28,29 and may be linked to high levels of obesity and hypertension. 28,30 Regarding our second observation, there is little information, to our awareness, relating circulating levels of the cardiac natriuretic peptides to ethnicity.…”
Section: Discussionsupporting
confidence: 51%
“…Where no exact match was available priority was given to age and ethnicity. Thus, 61 Emirates, 57 nGAs, 59 Africans and 89 SEAs (26,27,27, 48 hypertensives, respectively) were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Very few studies have monitored the activation of circulating biomarkers in patients admitted to cardiac rehabilitation, and these have mainly involved small series of patients with heart failure and led to conflicting results. A recent study of 95 heart failure patients found that 9 months of aerobic training significantly reduced the plasma concentrations of BNP and norepinephrine, 28 and a study of 44 MI patients enrolled in an exercise-based rehabilitation program also found a reduction in BNP levels; 5 conversely, a study of physical training involving of other cells, including smooth muscle cells and fibroblasts. 20 In addition, neutrophils contain a store of mature protein in their specific granules and can promptly release the molecule in response to proinflammatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is important to check whether each subject/patient has performed intense physical activity before cTn measurement. Troponin release after effort stress test may allow the identification of a subset of subjects at an increased risk of heart failure [57][58][59], and standardized physical effort with consequent cTn release variations may play an important prognostic role in patients with heart failure [57,58].…”
Section: Physical Exercisementioning
confidence: 99%